Disclosure practices among unit trust funds in Malaysia - Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar; Tayib, Mahamad; Lode, Nor Asma (Universiti Utara Malaysia, 2001)
This study examined the level of transparency among unit trust funds in Malaysia. Unit trust funds were the focus of this study due to its nature: unique, heavily regulated and rapidly growing. The study investigated the extent of disclosure in relation to the various mandatory and voluntary requirements and the roles of the specific characteristics of trust funds in explaining their level of disclosure in the annual reports. The findings showed that the level of disclosure increased rapidly within the period of study suggesting that trust funds were becoming more transparent.